Analytical commentary to the UNCITRAL arbitration rules - Binder, Peter (London : Sweet & Maxwell, 2013)
A comprehensive collection of commentary and legislative material on the UNCITRAL Arbitration Rules 2010.
Includes bibliographical references and index.
Keywords: United Nations Commission on International Trade Law; International commercial arbitration